Religion and property rights - Minárik, Pavol; Chalupníček, Pavel; Lipka, David; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2013)
Religion and post-communist transition are two of the many issues that have earned attention of economists and social scientist in the recent decades. This dissertation collects three papers dealing with different issues concerning religion and the transition. The first one attempts to assess the role of religion in the transition and its impact on country's success in this process; it also outlines opportunities for research in this field. The second paper tries to uncover the role of religion in formation of economic and social attitudes of the people in post-communist countries. Both papers conclude that religion matters; Western Christianity appears to be more compatible with market economy than Orthodox Christianity and Islam, although these two religions are not necessarily an obstacle. Finally, the third paper deals with religious participation in post-communist countries. It shows that religious behavior is not completely independent of economic conditions and religious revivals in the post-communist era can be interpreted in economic terms.
Vedoucí práce: Pavel Chalupníček
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: hospodářská politika [obor disert. práce]; disertace; dissertations